Pengaruh Metode Karyawisata Terhadap Kemampuan Bahasa Anak Usia Dini - ayu, sovia mas (Universitas Islam Negeri Raden Intan Lampung, 2018)
This research aims to determine the effect of study tour method on the language skills of children, especially on the aspect of speaking children aged 5-6 years at Ar-Raudah Playgroup and Kindergarten. This research is a quantitative research, with 64 children population. The method and skills of language is measured by questionnaire and observation. Correlation and t test hypothesis used to data analyzed with SPSS Statistics 17.0 program. The result of data analysis obtained r value = 0.770 > 0,207 with significance level 5%. t test yielded t value = 9,496 > t table 1,960. Thus result concluded that there are a positive influence between the method and the language skills of children aged 5-6 years, especially on speaking aspects at Ar-Raudah Playgroup and Kindergarten Bandar Lampung.